Efektifitas Kebijakan Pemekaran Wilayah Terhadap Peningkatan Pelayanan Publik - Rahmawati Kusuma (Jatiswara, 2011)
The Principle of local autonomy using the principle of broad outonomy.in the sense the area is given authority to manage and regulate all the affairs of goverment into the affairs of goverment beyond that specified in the law number 32 of 2004 on regional goverment. Region expansion is intended to realize the welfare of the community in the area and improve local democracy, and improve the effectiveness of public service in fact deviated from the purpose. lot of probem that arise in the expansion area, ranging from the problem associated with the legislation until at such implementation. But region expansion continues to flow and seem difficult dammed either by local goverment (parent) and goverment (interior ministry) parliaments and council representative also indicated that the space of regional area. Its not just a matter of goverment administration but also including with economic, political, including strong political dimension in the expansion area. It is therefore important to have a grand design the arrangement of the regions, associated with the central goverment,s role in controlling the formation of new outonomous regions in order to achieve the goals of ethablishing a new area,which realize the objectives of regional autonomy both political goals, economic and objectives of the central goverment and area.